2023
DOI: 10.1186/s40621-023-00447-4
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of demographic and background factors associated with the development of children’s aquatic competence

Abstract: Background Globally, drowning is a leading cause of unintentional injury and death among children. Teaching aquatic competencies (swimming skills and water safety knowledge) to children has been proposed as a prevention strategy. In Australia, however, many children are not meeting standard aquatic competency benchmarks. Exploration of the connection between demographic and background factors and aquatic competencies could provide insight into why differences in acquisition of aquatic knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In comparison to running, the smaller to nonexistent prepubertal sex-based differences in swimming may be partially explained by noting that swimming is a learned skill that requires access to facilities and coaching to a much greater extent than does the innate skill of running (Olaisen et al, 2018). Furthermore, Duke et al (2023) observed that in addition to sex, school type was a major factor influencing swimming skills since some schools, particularly smaller or less affluent schools, lack aquatic facilities. These authors also observed that frequency of participation in aquatic activity and prior negative aquatic experiences also contributed to the smaller prepubertal sex-based differences in swimming performance than other sports.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to running, the smaller to nonexistent prepubertal sex-based differences in swimming may be partially explained by noting that swimming is a learned skill that requires access to facilities and coaching to a much greater extent than does the innate skill of running (Olaisen et al, 2018). Furthermore, Duke et al (2023) observed that in addition to sex, school type was a major factor influencing swimming skills since some schools, particularly smaller or less affluent schools, lack aquatic facilities. These authors also observed that frequency of participation in aquatic activity and prior negative aquatic experiences also contributed to the smaller prepubertal sex-based differences in swimming performance than other sports.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Duke et al. (2023) observed that in addition to sex, school type was a major factor influencing swimming skills since some schools, particularly smaller or less affluent schools, lack aquatic facilities. These authors also observed that frequency of participation in aquatic activity and prior negative aquatic experiences also contributed to the smaller prepubertal sex‐based differences in swimming performance than other sports.…”
Section: Discussionmentioning
confidence: 99%